Do Participants With Low Back Pain Who Respond to Spinal Manipulative Therapy Differ Biomechanically From Nonresponders, Untreated Controls or Asymptomatic Controls?. Issue 17 (1st September 2015) - Wong, Arnold Y. L.; Parent, Eric C.; Dhillon, Sukhvinder S.; Prasad, Narasimha; Kawchuk, Gregory N.
Abstract : Study Design: Nonrandomized controlled study. Objective: To determine whether patients with low back pain (LBP) who respond to spinal manipulative therapy (SMT) differ biomechanically from nonresponders, untreated controls or asymptomatic controls. Summary of Background Data: Some but not all patients with LBP report improvement in function after SMT. When compared with nonresponders, studies suggest that SMT responders demonstrate significant changes in spinal stiffness, muscle contraction, and disc diffusion. Unfortunately, the significance of these observations remains uncertain given methodological differences between studies including a lack of controls. Methods: Participants with LBP and asymptomatic controls attended 3 sessions for 7 days. On sessions 1 and 2, participants with LBP received SMT (+LBP/+SMT, n = 32) whereas asymptomatic controls did not (−LBP/−SMT, n = 57). In these sessions, spinal stiffness and multifidus thickness ratios were obtained before and after SMT and on day 7. Apparent diffusion coefficients from lumbar discs were obtained from +LBP/+SMT participants before and after SMT on session 1 and from an LBP control group that did not receive SMT (+LBP/−SMT, n = 16). +LBP/+SMT participants were dichotomized as responders/nonresponders on the basis of self-reported disability on day 7. A repeated measures analysis of covariance was used to compare apparent diffusion coefficients among responders, nonresponders, and +LBP/-SMT subjects, as well as spinal stiffness or multifidus thickness ratio among responders, nonresponders, and −LBP/−SMT subjects. Results: After the first SMT, SMT responders displayed statistically significant decreases in spinal stiffness and increases in multifidus thickness ratio sustained for more than 7 days; these findings were not observed in other groups. Similarly, only SMT responders displayed significant post-SMT improvement in apparent diffusion coefficients. Conclusion: Those reporting post-SMT improvement in disability demonstrated simultaneous changes between self-reported and objective measures of spinal function. This coherence did not exist for asymptomatic controls or no-treatment controls. These data imply that SMT impacts biomechanical characteristics within SMT responders not present in all patients with LBP. This work provides a foundation to investigate the heterogeneous nature of LBP, mechanisms underlying differential therapeutic response, and the biomechanical and imaging characteristics defining responders at baseline. Level of Evidence: 3 Abstract : Supplemental Digital Content is Available in the Text.Participants with low back pain receiving spinal manipulative therapy were classified as responders or nonresponders on the basis of disability change scores. Compared with nonresponders and asymptomatic controls, spinal manipulative therapy responders had significantly decreased spinal stiffness and increased multifidus thickness ratios that were sustained over 1 week. Spinal manipulative therapy responders also demonstrated enhanced lumbar disc diffusion.